Case report: 11 years on hemodialysis with a 4-year-old baby girl: A success story - Mambap, Alex Tatang; Bechem, Efuetnkeng; Kan, Kate Mafor; Laah, Sylvain Njoyo; Sunjoh, Frida; Ashuntantang, Gloria Enow (Frontiers in Medicine, 2023)
Abstract: Despite advances in clinical management and dialysis care, the outcome of unplanned pregnancy in women on maintenance haemodialysis remains a difficult journey for the patient, foetus, and healthcare staff, particularly in low-resource countries.. We report the successful outcome of a pregnancy in an anuric woman on twice-weekly maintenance haemodialysis for chronic glomerulonephritis since November 2012 in Cameroon. She was discovered pregnant at 18 weeks of gestation. The pregnancy was maintained until 36 weeks when a healthy 2270g female baby was delivered by elective caesarean section for tight nuchal cords and intrauterine growth retardation. The mother's post-partum period was uneventful. Except for hypoglycemia shortly after birth, the baby was fine. The patient is still on haemodialysis after four years, and the baby is healthy and attending school.